Pottery micro enterprises and their level of profitability the case of Pot Makers of Lezo, Inc. - de la Mota, Mutya P.
Any business enterprise aims for the generation of earnings that will ensure sustainability of the operations. Profit means the ability to sustain an enterprise and speak of its efficiency. The measure of proofitability will provide information on the viability of the enterprise, manageriaal performance and market opportunities. Like any micro enterprise, pot makerss in the municipality of Lezo in the Province of Aklan, aim for profits in their business ventures. the potteyr industry in Lezo has developed considerably with the support and assistance of government and non-government agencies. Potteyr entrepreneurs and other stakeholders partner in developmental projects and activities. Parallel to the objective of industry growth, a defined measurement of profitaility will aid in evaluation of productivity and sustainability. The case study on the Pot Makers Association of Lezo, Inc., and their level of profitability revealed the progressing profitability of the pottery micro enterprises for the 3-year period 2005 to 2007. This was supported by the increasing figures of sales volume, gross profit and net profit margins. Factors related to management, production, marketing, financial and areas for improvement impact business operations of pottery micro enterprises. However, pottery entrepreneurs see promising opportunities for them. Financial and technical support to the pottry enterprises and the industry as a whole will further enhance productivity and usher in bigger business opportunities.